Virtual robot: Virtual becomes reality - Mohamad, N.; Yusof, S. A. M.; Che Mat, Ruzinoor (2002)
One of the benefits that education reaps from Virtual Reality (VR) is the ability to visualize,simulate and interact with virtual objects.This ability allows the students to have the trial and error session before actually practicing it on real things.Here comes to the point where the idea of having virtual robot in assisting students learning emerged.Instead of studying the physical robot in class, students can study the virtual robot on computer at home prior to class or even in the class itself.Students can immerse themselves in this digitized world; experience the sense of moving and becoming part of the robot system.This paper presents the methodology for the whole-robot 3D graphics design, integration between the object modeling to VR and the construction of real-time behavior and interactivity modification to accommodate changes in the virtual environment.